2014
DOI: 10.2135/cropsci2013.10.0678
|View full text |Cite
|
Sign up to set email alerts
|

Winter Canola Yield and Survival as a Function of Environment, Genetics, and Management

Abstract: Successful winter canola (Brassica napus L.) production creates diversity and provides crop rotation alternatives for producers. Stand establishment and winter survival are among the main determinants of success in winter canola production. The objective of this research was to investigate the impact of environment, crop management, genetics and their interactions on canola stand establishment, survival, yield, and oil and protein content. Two datasets were analyzed: results from the National Winter Canola Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 16 publications
2
41
1
Order By: Relevance
“…The model predictions should therefore be treated cautiously until further field validation is conducted. Single plot yields close to 6000 kg/ha have been observed by our research group in California, however, and seed yields from canola of close to 8000 kg/ha are reported by other workers (Assefa et al, 2014;Christy et al, 2013;Jones, 2008), and APSIM can accurately simulate canola yields up to 7500 kg/ha (Robertson and Lilley, 2016).…”
Section: Irrigated Production Scenariossupporting
confidence: 63%
See 1 more Smart Citation
“…The model predictions should therefore be treated cautiously until further field validation is conducted. Single plot yields close to 6000 kg/ha have been observed by our research group in California, however, and seed yields from canola of close to 8000 kg/ha are reported by other workers (Assefa et al, 2014;Christy et al, 2013;Jones, 2008), and APSIM can accurately simulate canola yields up to 7500 kg/ha (Robertson and Lilley, 2016).…”
Section: Irrigated Production Scenariossupporting
confidence: 63%
“…The longterm mean yield of canola in the United States (North Dakota, Oklahoma, Minnesota, Idaho, Montana) for all years in which data was available at the time of writing was approximately 1700 kg/ha, with no difference between predominantly warmor cool-season production (USDA NASS, 2015). For further comparison, the mean yield of canola from the U.S. National Winter Canola Variety Trials between 2003 and 2012 was 2000 kg/ha (Assefa et al, 2014) and the mean yield for topperforming winter canola in multi-environment trials in North Carolina was 1800 kg/ha (George et al, 2012).…”
Section: Rain-fed Production Scenariomentioning
confidence: 99%
“…In this regard, winter camelina may be like winter canola. Assefa et al (2014) suggested that planting winter canola early enough to provide adequate autumn growth may increase its winter survival, but that excessive growth by planting too early, or limiting growth by planting late, may be detrimental. However, for winter camelina, more research is needed to determine both biological and physical factors effecting its winter survivability.…”
Section: Crude Proteinmentioning
confidence: 99%
“…Camelina oil has been shown to be suitable for both diesel and jet fuel production (Moser, 2010;Krohn and Fripp, 2012) as well as for cooking oil (Pilgeram et al, 2007). Lastly, canola seed has 40% oil by weight composed of 60, 20, and 10 wt/wt% oleic, linoleic, and linolenic acids, respectively (Mag, 1983;Rife and Shroyer, 2000;Assefa et al, 2014). Canola oil is used in products such as cooking oil, margarine and shortening, and salad oil and also can be used for biodiesel production (Eskin and McDonald, 1991).…”
Section: Tablementioning
confidence: 99%
“…The canola in SD 2013 had 16% green cover but did not produce any yield, which likely was due to seeds germinating after they were frost-seeded but not receiving adequate vernalization to induce flowering. Winter canola is on the edge of its adaption to cold hardiness in this region, and despite potential yields of >2 Mg ha −1 (Rife and Shroyer, 2000;Assefa et al, 2014), this plant needs additional breeding to become sufficiently winter hardy to reach such yields in the NCB.…”
Section: Yieldmentioning
confidence: 99%